Formação e trabalho docente: da crítica ideal à crítica construida - LIPOVETSKY, Noêmia (2011)
This paper linked to the research line Work, Education, and Social Movements , of the Post Graduate Program in Education at Universidade Federal de Goiás (UFG), aims to investigate the relationship between training and teaching work seeking to discern how the students from the Pedagogy School of the Education Faculty (FE/UFG), who are already working in the field of education, understand the society today and inside it the role of education and teaching work, by the highlighting of the critical capacity built by the subjects, through the intended ideal by the training course. The issue of the building of the critical capacity of the individuals is analyzed by the understanding of the movement for social changes related to education (and its possible engagement in it), from the perspective of radical changes which need to be operated in the theoretical and practical field of the production that today supports the work submitted to the capital. In this sense following the theoretical and methodological principles of the dialectical historical materialism, was used in the related study, specially the emanated reference from the works of Marks, Engels, Gramsci, Makarenko, Pistrak and Mészáros, as well as others like Frigotto, Gentili, Mancebo, Mascarenhas, Sguissardi, Tumolo and documents produced by the National Union of Teachers of Higher Institutions (ANDES). The research reveals that the investigated individuals conceive the society ruled by the capital as a model that need to be argued and improved and not exalted and the social role of education and the teaching work as subservient to this specie of society connected to the reproduction movement of the social relationships that maintain it in running. This role is manifested in the perspective of the education for citizenship as well as the expectation of the individuals constitution able to act according to the requirements and rules of current labors and other activities of the social life that requires formation of adapted minds, creativity and flexibility, besides preparation of the competence and abilities for the acquisition means to engage in the employability logic in the globalized world. Thus the elaborated conceptions by the subjects are connected by themselves to the correction aspects of the distortions and adequacy of the proposed training to the needs imposed by the work field where they act as educators (as a divergent way to the ideal training course proposed by the project of the investigated course) revealing the criticisms construction that in fact, has little or almost anything to contribute in the struggle by the society transformation, dominated by the capital. Such situation indicates the urgent necessity to transcend the vogue education, redefining the purpose of the educational work toward the building of another radically different of the existing one. Only that way the education could contributes to break with the logic focused on the capital.